Elimelech or Abimelech?: A Study on the Textual Variant of the Name of Noemin’s Husband in LXX-Ruth - Bonanno, Beatrice (Biblische Zeitschrift, 2021)
This paper analyses the textual variant of the name of Noemin’s husband in the book of Ruth: Elimelech according to the Masoretic Text and Abimelech according to the Septuagint. It investigates if this textual variant is linked to a different Hebrew Vorlage, whether it is carried out during the process of translation of the text in its Greek form, or whether it is due to its transmission in its Greek form. Finally, this study analyses the literary criticism of this variant by showing how a coherent character is created by name and through actions and how, in this way, God’s presence is accentuated in the narrative.